What Can We Say about 112,000 Taps on a Ndjebbana Touch Screen? - Auld, Glenn (The Australian Journal of Indigenous Education, 2002)
Abstract This paper reports on the use of touch screens to display simple talking books in a minority Indigenous Australian language. Three touch screens are located in an informal context in a remote Indigenous Australian community. The popularity of the computers can be explained by the form of the touch screen and by the intertextual and hybrid nature of the talking books. The results suggest the Kunibídji choose to transform their own culture by including new digital technologies which represent their social practice.